Regional Forest Governance of Industrial Plantation Forest (HTI) Development in Jambi Province - Suci Rahmadani (CV. Abhinaya Indo Group, 2026)
This study aims to analyze the impact of Industrial Plantation Forest (HTI) development on deforestation in Jambi Province and the role of forestry governance in influencing the relationship between the two. The study used a qualitative method with a literature study approach (library research) sourced from scientific journals, books, policy documents, and reports from related institutions. Data were analyzed descriptively and qualitatively through the stages of data collection, reduction, presentation, and drawing conclusions. The results show that HTI development contributes to deforestation through the conversion of natural forests to industrial plantations, changes in land use, and a decline in forest ecological quality. However, deforestation in Jambi is also influenced by other factors such as plantation expansion and infrastructure development. In addition, forestry governance plays a significant role in determining the level of HTI impact on deforestation. Effective governance can reduce pressure on forests, while weak governance has the potential to accelerate the rate of deforestation. Therefore, strengthening forestry governance is needed to support sustainable forest management in Jambi Province.